Effect of Nano-Selenium on meat quality of pigs - XIA Mei-sheng; ZHANG Hong-mei; HU Cai-hong (浙江大学学报. 农业与生命科学版)
A total of 234 finishing pigs (Duroc × Landrance × Yorkshire) were used to investigate the effects of nano elemental selenium (Nano-Se) or sodium selenite (Na2SeO3) on meat quality. The pigs were allocated to 13 treatments, each of which had 3 pens of 6 pigs per pen. Of the 13 treatments, one was the treatment in which the pigs were feeded with basal diet containing 0.046 mg/kg Se and served as control. Pigs in each of six experimental treatment were given, besides basal diet, 0.10, 0.20, 0.30, 0.40, 0.50 or 1.00 mg/kg supplemental Se in the form of Na2SeO3 and pigs in each of the other six experimental treatments were given the same concentration range of supplemental Se in the form of Nano-Se. The results were as follows: (i) When Na2SeO3 was added to the diet, drop loss of muscle decreased with the concentration of Se at the concentration range of 0-0.20 mg/kg and increased at the range of 0.30-1.00 mg/kg Se. Supplementation with 1.00 mg/kg Se as Na2SeO3 increased (P<0.05) drop loss as compared with the addition of Se in the concentration range of 0.20-0.50 mg/kg. When Nano-Se was added to the diet, drop loss remained steady at the peak value even at a concentration of 1.00 mg/kg Se. The pigs had lower (P<0.05) drop loss in the concentration range of 0.40-1.00 mg/kg as Nano-Se than as Na2SeO3. (ii) There were no significant difference in activities of glutathion peroxidase (GSH-Px), total antioxidative competence (T-AOC) and malondialdehyde (MDA) of muscle between the treatments of Nano-Se and Na2SeO3 when the added concentration of Se was 0.10-0.30 mg/kg. The pigs had higher (P<0.05) GSH-Px and T-AOC activities and lower (P<0.05) MDA activity in the concentration range of 0.40-1.00 mg/kg as Nano-Se than Na2SeO3. (iii) There were no difference in Se content of muscle between the treatments of Nano-Se and Na2SeO3 when the added concentration of Se was 0.10-0.30 mg/kg. The pigs had higher (P<0.05) Se content of muscle in the concentration range of 0.40-1.00 mg/kg supplied as Nano-Se than as Na2SeO3. (iv) Supplentation with Se increased the myoglobin content of muscle, however, the extent of increase was not affected by Se sources or the added concentration of Se. The results implicated that the optimal concentration range of Weinberg curve for Nano-Se is wider than that for Na2SeO3 and supplentation with high level of Nano-Se improved the antioxidant capacity, decreased drop loss and increased Se content of muscle as compared with Na2SeO3.